Refugees in International Law - Eishan Jan, Mohammad Naqib (2015)
Refugee’ in international legal system is a ‘status’. When a person or an ‘asylum seeker’ is granted this status he/she enjoys protection under a special branch of international law known as international refugee law, the centre peace of which is the 1951 Convention, as amended by its 1967 Protocol. IHRL and IHL may also afford protection to refugees – the former applies at all times and the later may provide refugees with protection in time of armed conflicts Islamic legal system also contain provisions governing the status of refugees and offers a number of mechanisms for their care and protection. But before we discuss the Islamic perspective of refugee protection it would not be out of the scope of my presentation to discuss briefly the term refugees in general and the protection afforded to them by the international refugee law.